Positive screening and carrier results for the England-wide universal newborn sickle cell screening programme by ethnicity and area for 2005–07. Issue 7 (30th June 2010) - Streetly, Allison; Latinovic, Radoslav; Henthorn, Joan
Abstract : Aims: The overall aim of the new national newborn programme is to identify infants at risk of sickle cell disease to allow early detection and to minimise deaths and complications. Methods: Universal screening for sickle cell disease was introduced in England between September 2003 and July 2006. The 13 newborn laboratories each screen between 25 000 and 110 000 babies a year using the existing dried bloodspot cards. The specified conditions to be screened for include sickle cell anaemia (Hb SS), Hb SC disease, Hb S/ β thalassaemia, Hb S/D Punjab and Hb S/O Arab . Data are reported on screening results by ethnic group and geographical area. Results: The prevalence of screen positive results across England is 1:2000. There is a 25-fold variation by geographical area. African babies make up 61% of all screen positive results despite representing only 4% of total births. Combined carrier rates vary widely by ethnicity, from 1.85 per 1000 (1:540) in 'White British' to 145 per 1000 (1:7) in 'African' babies. Refusal rates for screening show variation by ethnicity. Conclusions: These results provide useful information both about the frequency of these conditions and the carrier state and their geographic and ethnic distribution across England. This can be used to refine counselling information and are also useful to target and plan services and public information.